Murine interfollicular epidermal differentiation is gradualistic with GRHL3 controlling progression from stem to transition cell states - Ziguang Lin (Nature Portfolio, 2020)
The interfollicular epidermis (IFE) is part of the epidermis but how it forms is unclear. Here, the authors perform scRNA sequencing at various developmental stages on the mouse epidermis and on deletion of Grhl3, showing IFE differentiation is gradual and that Grhl3 is needed for commitment to differentiation by regulating Wnt signalling pathway.